Effect of Malathion Against Sal Seeds Weevil, Sitophilus rugicollis in Storage and its Persistence - Choubey, Veena; Bhandari, Rita; Kulkarni, Nitin; Mishra, Vinod Kumar (Asian Journal of Biological and Life Sciences, 2014)
Sal (Shorea robusta Gaertn. f.) is an important tree species in India being used for its timber and Non Timber Forest Products specially seed which are often attached by different damaging insect pests in storage. Present study deals with the effect of malathion against the adults, eggs and other developmental stages to control serious seed weevil, Sitophilus rugicollis of Sal, Shorea robust seeds in storage. Sal seeds were sprayed or fumitated (air fumigation) with malathion EC 50 in different concentrations ranging from 0.0025 to 0.2 %) in glass jars and adults were release for the egg laying and further development. Observations were recorded on mortality of eggs, mortality of developmental stages and reduction in emergence of adults by the direct exposure and persistence effect of the fumigation up to 14 weeks. Highest concentration, 0.1 and 0.2% caused significant reduction in emergence of weevil adults. Similarly 0.1 and 0.2% concentration of fumigant caused 90.64 and 100% mortality in eggs respectively. All the treatments of malathion were effective causing 100% adult mortality compared to control, when adults were exposed directly to freshly treated seeds. Persistence of malathion after fumigation in storage was evaluated till 14 subsequent weeks. Persistence of malathion at 0.1% concentration was observed with 100% mortality in adults. Paper deals with the utility of malathion for controlling the infestation of sal seed weevil in the storage.
Keywords: Dichlorvos; forest seeds; Seed borers; seed protection; stored seed.